ANALISIS PENGARUH FAKTOR TERHADAP ENTREPRENEURIAL INTENTION MAHASISWA MANAJEMEN DI SURABAYA - Darwis, Justin; Whidya Utami, Christina (PERFORMA, 2024)
Growth mindset asserts that abilities can be developed over time, contrasting with a fixed mindset that views abilities as inherent and unchangeable. This quantitative study investigates the relationship between growth mindset, self-efficacy, entrepreneurial education, economic development, and entrepreneurial intention among management students. The sample consists of 130 students, calculated using Hair’s formula. Data is collected through questionnaires using a Likert scale. Statistical analysis using SPSS includes tests for validity, reliability, normality, multicollinearity, autocorrelation, heteroskedasticity, and goodness of fit, followed by t-tests and ANOVA. Results show that growth mindset and self-efficacy do not directly predict academic performance and career interest but contribute positively when combined with other variables like entrepreneurial education and economic development. Entrepreneurial education positively influences entrepreneurial intention, as supported by previous research. Economic development also significantly impacts entrepreneurial intention, especially in developing countries with numerous business opportunities. The study highlights the need for comprehensive entrepreneurial education combining theoretical knowledge with practical experience to foster entrepreneurial intention among students. It also underscores the importance of economic development in providing a conducive environment for entrepreneurship. Further research should explore mediating and moderating variables to understand the complex interplay between these factors better.